Distribution and species richness of a forest raptor community in relation to urbanization - Bosakowski, T.; Smith, D.G. (Journal of Raptor Research, 1997)
We studied the species richness and distribution of the forest raptor community in a New Jersey watershed in relation to urbanization. Raptors were systematically surveyed using high volume broadcasts of conspecific and heterospecific calls during the breeding season at a total of 81 survey stations. Ten habitat variables relevant to urbanization were measured at each survey station using topographic maps and aerial photographs. Results showed a community composed of 10 species of breeding raptors. Buteo lineatus, Accipiter gentilis and Strix varia showed a significant avoidance of suburban habitat, whereas B. jamaicensis and Bubo virginianus had a greater tendency to occupy such areas. Lowland habitat was significantly selected by S. varia, B. lineatus and A. cooperii, a habitat usually most susceptible to development in the study region. Raptor species richness showed a strong positive correlation (r = 0.79, P < 0.01) with wilderness area size. No wilderness area less than 1000 ha had more than four raptor species while four to eight species were found in areas from 1000-8000 ha. Utilization of three increasing size classes of wilderness areas showed increasing trends for B. lineatus, A. gentilis and S. varia, and decreasing trends for B. jamaicensis and Bubo virginianus. © 1997 The Raptor Research Foundation, Inc.
Keywords: Community; Forest fragmentation; Forest raptors; Survey; Urbanization; Wilderness; dept.bio; ⛔ No DOI found

First record of Anthopotamus verticis and new records of A. Distinctus (Ephemeroptera: Potamanthidae) in New England - Burian, S.K. (Entomological News, 1997)
The species Anthopotamus verticis is recorded for the first time in New England from the Housatonic River in western Connecticut. Notes on the larval habitat and observations on the sympatric occurrence of this species with A. distinctus are presented. New distribution records for A. distinctus are presented for Massachusetts and Vermont.
Keywords: Anthopotamus distinctus; Anthopotamus verticis; dept.bio; ⛔ No DOI found

New record of Brachycercus maculatus berner (Ephemeroptera: Caenidae) from New York and a key to larvae of northeastern species - Burian, S.K.; Novak, M.A.; Bode, R.W.; Abele, L. (Great Lakes Entomologist, 1997)
Brachycercus maculatus, a member of a rare group of mayflies, is now recorded for the first time from New York State in the upper Hudson River. An illustrated key to the Brachycercus larvae of northeastern North America is provided to spur further study of the genus in the region.
Keywords: Brachycercus maculatus; dept.bio; ⛔ No DOI found

The summer stars program - Cantrell, M.L.; Ebdon, S.A.; Firlik, R.; Johnson, D.; Rearick, D. (Educational Leadership, 1997)
Space, futurism, exploration, and stardom are some of the themes at a summer camp inspired by Howard Gardner's theories.
Keywords: dept.bio; dept.edu; peer-reviewed; ⛔ No DOI found